Pengaruh Pelaksanaan Kangaroo Mother Care (KMC) Selama Satu Jam Terhadap Suhu Tubuh Bayi Berat Badan Lahir Rendah (BBLR) Di Ruang Perinatologi RSUD Pandan Arang Boyolali - Setiyawan Setiyawan; Wahyu Deda Prajani; Wahyu Dwi Agussafutri ((JKG) Jurnal Keperawatan Global, 2019)
Background: Low birth weight has the highest contribution to neonatal mortality rate. One of its complications is body temperature instability, and to maintain it, the infants are exposed to the Kangaroo Mother Care (KMC) method. The objective of this research is to investigate the one-hour KMC implementation on the body temperature of low birth weight infants at the Perinatology Room of Pandan Arang Local General Hospital of Boyolali. Method: This research used the quasi experimental method. It was conducted from October to November 2016. Its samples consisted of 22 infants and were determined through the accidental sampling technique. Its data were analyzed by using the Wilcoxon signed ranks test. Result: The result of the research shows that the average body temperatures prior to and following the implementation of one-hour KMC in Days 1, 2, and 3 were 36.660C and 37.070C. There was an effect of the implementation of one-hour KMC on the body temperature of low birth weight infants as indicated by the p-value which was less than 0.05. Conclusion: Thus, the future research is expected to develop the research by adding the research variables that may influence the body temperature stability of low birth weight infants in addition to the one-hour KMC.